Genetic diversity in soybean genotypes with resistance to Heterodera glycines - Ana Paula Oliveira Nogueira; Rita de Cássia Teixeira Oliveira; Rosângela D’Arc de Lima Oliveira; Cosme Damião Cruz; Tuneo Sediyama; Éder Matsuo (Crop Breeding and Applied Biotechnology, 2011)
The purpose of this study was to analyze the genetic diversity among soybean genotypes inoculated with Heteroderaglycines race 3. The experiments were conducted in a greenhouse. In two performance tests of morphological characteristics andresistance to the pathogen, 27 soybean genotypes were assessed. The coefficient of genotypic determination was estimated by themethod of analysis of variance and the genetic diversity analyzed based on dendrograms and optimization method. The estimatedcoefficients of determination indicated a predominantly genetic origin of the genotypic differences in the traits. The genetic variabilitywas maintained in the superior genotypes, which can be used in breeding programs for resistance to soybean cyst nematode